All Days 1994
DOI: 10.2118/28068-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Sand Production Processes Near an Orifice

Abstract: An experimental study was performed using Ottawa sand and a produced sand. A 3-D semi-analytical flow model was developed to analyze the experimental data. The results show that the ratio of sand grain size and outlet hole size, grain size distribution, and angularity are the most important factors affecting the sand arch stability. Pressure increase mode and pressure magnitude also affect arch stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Larger openings require larger grains to form stable arches. The selection of opening diameters is used as a sand-production-control design strategy (Penberthy and Shaughnessy 2002;Yim et al 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Larger openings require larger grains to form stable arches. The selection of opening diameters is used as a sand-production-control design strategy (Penberthy and Shaughnessy 2002;Yim et al 1994).…”
Section: Resultsmentioning
confidence: 99%
“…The stress in the arches/bridges is better transmitted for larger sand grains. It has been reported previously that besides the flow rate, the arch stability is strongly dependent on the granulometry of the porous material and the size of the perforation 11,12,15 . Larger perforations required larger grains to form stable arches.…”
Section: Effect Of Morphology and Size Distributionmentioning
confidence: 97%
“…For round sand, arching was not observed either for a loose or dense pack at low loads. Yim et al 11 observed that in addition to the flow rate, the arch stability is strongly dependent on the granulometry of the sand and on the size of the perforation. Larger perforations required larger grains to form stable arches.…”
Section: Introductionmentioning
confidence: 99%
“…al 48 found that the grain size distribution and angularity were important in forming stable arches in unstressed sand. However, their transparent cell provided no ability to apply closure stress to the proppant.…”
Section: Potential To Flowbackmentioning
confidence: 99%